Importance-Performance Analysis: Upaya Peningkatan Kualitas Layanan - Dina Lusianti; Mia Ajeng Alifiana (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
Service quality, although intangible, remains crucial, so this study aims to find out student satisfaction index numbers and attributes that need to be followed up to improve the quality of service. The sample of 337 students from the Faculty of Economics and Business, Universitas Maria Kudus who were still active. The method used is the Importance-Performance Analysis approach. The results of this study prove that students have felt satisfied with the services provided.